Angiopoietin-2 expression and its relationship with lymphangiogenesis and clinicopathological characteristics in cutaneous malignant melanoma - Zheng, Wei; Ju, Wei; Yang, Xi-Hu; Yan, Zhi-Xin (Frontiers in Oncology, 2023)
Objective The aim of this study was to investigate angiopoietin-2 (Ang-2/ANGPT2) expression and its relationship with lymphangiogenesis and clinicopathological characteristics in cutaneous malignant melanoma (CMM). Methods Gene expression differences between metastatic melanoma and melanoma in situ in 472 patients from the TCGA database were analyzed. The target gene Ang-2 was screened. A clinical study was conducted to analyze the correlation between Ang-2 expression in CMM and tumor-associated lymphangiogenesis. A total of 42 patients with primary CMM who underwent extended tumor resection procedures at the Affiliated Hospital of Jiangsu University were included in this study. Clinical data (gender, age, lymph node metastasis, Breslow thickness, and clinical stage) were collected. The expression levels of both Ang-2 and lymphatic vessel endothelial hyaluronan receptor-1 (LYVE-1) proteins were detected by immunohistochemistry (IHC). Lymphatic vascular density (LVD) was counted by using LYVE-1 to label lymphatic endothelial cells (LECs) in peritumoral and intratumoral areas per high-magnification field of view. Statistical analysis was performed using the Pearson correlation test and Student’s t-test. Results Using the TCGA database, it was found that the gene expression level of Ang-2 in 368 cases of metastatic melanoma was significantly higher than that in 104 cases of melanoma in situ. Correlation analysis showed a significant relationship between Ang-2 and LYVE-1, and vascular endothelial growth factor receptor 3(VEGFR3) expression, respectively, in CMM. Moreover, the optimal cutoff value of survival analysis showed that high Ang-2 expression in CMM had a worse prognosis, based on data from the TCGA database. Our research showed that Ang-2 was more highly expressed in the group of patients with lymph node metastasis and in the group of stage 3C-4 patients than in the group of patients with no lymph node metastasis and in the group of stage 0-3B patients. Our research also showed that LVD in the group of patients with lymph node metastasis and in the group of stage 3C-4 patients was significantly higher than that in the group of no lymph node metastasis and in the group of stage 0-3B patients, respectively. Breslow thickness also correlated with Ang-2 expression and LVD. Ang-2 expression was not related to sex or age. Ang-2 expression was obviously correlated with LVD. Conclusion An evaluation of Ang-2 expression and LVD can be used to predict the risk of tumor lymphatic metastasis and determine the prognosis of CMM. These results may also provide a new clinical treatment strategy for CMM.